Значения и синтаксические функции именительного падежа (На материале русского и литовского языков) - Михальченко, В. (Kalbotyra, 1973)
In the article the meaning and syntactical functioning of the nominative case in the Lithuanian and Russian languages are analysed.The results of the analyses have displayed that the subject - predicate functions are equal in both languages. Besides, the Lithuanian nominative case has the object - adverb function.The analysed language material has indicated that the Lithuanian nominative case as a case of the subject is grammatically less exactly shaped than the Russian nominative case.